Areal differentiation in crime in public transit terminals in Ibadan metropolis (2013)
The unprecedented rate of urbanization in the twentieth and twenty- first century in most less developed countries (LDC) is coming at a huge cost to cities in these countries chief among which are distorted morphologies, dysfunctional infrastructural system and ever-increasing crime rate. In Ibadan metropolis one of the infrastructure that has been subject of this systemic abuse are the public transit terminals, this study analyses the incidences of crime, the spatial pattern of their occurrences and the nature of crime which are prevalent in and around major road transit terminals, statistical records of crime incidences and data on crime experiences of two hundred and fifty respondents were analyzed statistically and descriptively, the findings revealed that crime rate, the nature and pattern of occurrence varied spatially within the metropolitan parks, recommendations on how best to safeguard the parks are subsequently made.